The effect of make-a-match cooperative model on elementary school civic lectures reviewed from students’ critical and democratic thinking - Gandamana, Apiek; Fathurrohman; Nurhayati (Universitas Jambi, Indonesia, 2025)
This research aimed to determine the effect of critical and democratic thinking abilities on students using the 'make-a-match' learning model and those using the lecture model. The research sample was 94 students of PGSD classes F and E. The research employed questionnaires and interviews as its primary research instruments. Based on the research results, there is evidence that the treatment (experiment) significantly affected the critical and democratic thinking skills of students who were given the treatment. Furthermore, the results of the paired t-test and comparison of the post-test scores of students who took part in the research using the make-a-match learning model were a score of 89.48, compared to the lecture/text learning model, with a score of 66.89. In conclusion, the make-a-match learning model affects the critical and democratic thinking abilities of prospective elementary school teacher students.